Violent offending in borderline personality disorder and attention deficit/hyperactivity disorder. (15th September 2019) - Sebastian, Alexandra; Retz, Wolfgang; Tüscher, Oliver; Turner, Daniel
Abstract: The prevalence of borderline personality disorder (BPD) and attention deficit/hyperactivity disorder (ADHD) is significantly higher among offenders compared to the prevalence found in the general population. Both disorders share important diagnostic characteristics and thus it has been suggested that they might follow a common developmental pathway. In this narrative review, we first discuss the potential links of disorder inherent symptoms such as impulsivity and emotion regulation difficulties and how they might elevate the risk of violent delinquency. We continue with highlighting that comorbidities particularly from the antisocial spectrum as well as comorbid substance use disorders need to be considered in the context of offending in individuals with BPD and ADHD. Finally, we summarize current therapeutic approaches for offenders with BPD and ADHD and associated challenges especially concerning the provision of treatment in prison settings. This article is part of the Special Issue entitled 'Current status of the neurobiology of aggression and impulsivity'. Highlights: BPD and ADHD are both overrepresented among offenders. Emotional dysregulation mediates violent behavior in BPD. Response inhibition deficits likely increase the risk for offending in ADHD. Antisocial conditions potentiate the risk for offending behaviors for BPD and ADHD. Conveying impulse control and problem-solving skills may reduce high treatment drop-out rates.